Higher Education Financing and the Educational Aspirations of Teenagers and their Parents - Dan Anderberg; Arnaud Chevalier; Lena Hassani Nezhad; Melanie Lührmann; Ronni Pavan (Institute of Labor Economics (IZA), 2020)
We study the impact of higher education financing on the academic aspirations of teenagers and of their parents. We exploit a reform which introduced a large increase in the maximum university tuition fees and a more redistributive student loan system, both of which varied across the UK's constituent countries. Using rare survey data on postcompulsory secondary and university education aspirations, we find that teenagers' aspirations are not responsive to large changes in higher education financing. In contrast, the socio-economic gap in parental aspirations for their childrens' education is reduced through the reform, in accordance with the redistributive financing policies set by policy-makers.
Keywords: I23; I22; I24; J24; D84; 330; education aspirations; university cost; access to higher education